Volunteer Responder Recruitment, Voluntary Deployment of Automated External Defibrillators, and Coverage of Out‐of‐Hospital Cardiac Arrest in Denmark - Nanna Bo; Anne Juul Grabmayr; Fredrik Folke; Louise Kollander Jakobsen; Julie Samsøe Kjølbye; Shaun Theodor Florentz Sødergren; Kristian Bundgaard Ringgren; Linn Andelius; Christian Torp‐Pedersen; Mads C. Tofte Gregers; Carolina Malta Hansen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background A volunteer responder program to out‐of‐hospital cardiac arrest (OHCA) was implemented stepwise in Denmark (2017–2020). This study assessed automated external defibrillator (AED) and volunteer responder coverage of historical OHCAs in Denmark. Methods Non‐emergency medical services witnessed OHCAs (2016–2020) from the Danish Cardiac Arrest Registry with known location and AEDs from the Danish AED network were included. Volunteer responders with an exact location were identified using the volunteer responder server. A historical OHCA was defined as covered when ≥4 volunteer responders and ≥1 AED were <500 m range. Coverage was examined according to location (public or home), time of day (noon or midnight), and volunteer responder background (lay people or health care professionals). Results A total of 22 330 OHCAs and 22 418 AEDs (387 AEDs/100 000 inhabitants) were included. At noon, 34 180 volunteer responders (589 volunteer responders/100 000 inhabitants) were identified as available. During daytime, OHCA coverage was 56% (95% CI, 55.9–57.2, n=12 625) decreasing to 30% (95% CI, 29.8–31.0, n=6793) when including only volunteer responders with a health care background. There was no significant difference in coverage according to time of day or location of arrest. OHCA coverage was 85% (95% CI, 84.2–86.0, n=6153) 4 years after implementation (first area included). Conclusion Regardless of time of day, more than half of all OHCAs were covered by volunteer responders and AEDs in Denmark. Excluding lay volunteers would almost halve the coverage. Our results indicate successful recruitment of volunteer responders and deployment of AEDs with great potential for improving bystander defibrillation.